2008
DOI: 10.1016/j.neulet.2008.01.026
|View full text |Cite
|
Sign up to set email alerts
|

Extraordinary large brains in tool-using New Caledonian crows (Corvus moneduloides)

Abstract: A general correlation exists between brain weight and higher cognitive ability in birds and mammals. In birds this relationship is especially evident in corvids. These animals are well-known for their flexible behavior and problem-solving abilities, and have relatively large brains associated with a pallial enlargement. At the behavioral level, New Caledonian crows stand out amongst corvids because of their impressive object manipulation skills both in the wild and in the laboratory. However, nothing is known … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 78 publications
(39 citation statements)
references
References 41 publications
(58 reference statements)
1
38
0
Order By: Relevance
“…NC crows also appear to have relatively large brains, even among highly encephalized corvids (Cnotka, Güntürkün, Rehkämper, Gray, & Hunt, 2008;Mehlhorn et al, 2010). In the wild, NC crows are one of the few species that habitually manufacture tools, and the diversity of tools that they manufacture is matched only by chimpanzees (Whiten et al, 1999) and orangutans (van Schaik et al, 2003).…”
Section: Jennifer C Hmentioning
confidence: 99%
“…NC crows also appear to have relatively large brains, even among highly encephalized corvids (Cnotka, Güntürkün, Rehkämper, Gray, & Hunt, 2008;Mehlhorn et al, 2010). In the wild, NC crows are one of the few species that habitually manufacture tools, and the diversity of tools that they manufacture is matched only by chimpanzees (Whiten et al, 1999) and orangutans (van Schaik et al, 2003).…”
Section: Jennifer C Hmentioning
confidence: 99%
“…Cnotka et al (2008) reported that the NC crow's brain was relatively larger than the brain of the carrion crow (C. corone), but questions have been raised about the statistical methods that were used (Medina, 2013). More recent data show that the NC crow's brain size (mean of 7.56 g for 5 birds averaging 277 g bodyweight; Cnotka et al, 2008) is comparable to that of the considerably larger rook (C. frugilegus) introduced into New Zealand (mean of 7.60 g for 5 birds averaging 456 g bodyweight; GRH unpublished data). This comparison suggests that the NC crow has a brain relatively larger than at least one other Corvus species.…”
Section: Figures 1c and 1d)mentioning
confidence: 99%
“…The traditional approach has been to make gross comparisons of overall brain volume relative to body size, usually factoring in that smaller animals have a larger surface area compared to their volume, resulting in proportionally larger brains (e.g., Jerison, 1973). The resulting encephalization quotient comes in several versions; regardless, animals thought of as cognitively complex -including the four groups we are discussing -always have brains larger than expected from their body size (e.g., Cnotka, Güntürkün, Rehkämper, Gray, & Hunt, 2008;Iwaniuk & Hurd, 2005;Marino, 2002;Roth & Dicke, 2005). Brain-to-body-size measures have been used to find many correlations with varying types of behavioral flexibility (e.g., Reader & Laland, 2002;Sol, 2009).…”
Section: Parallel or Convergent Brains?mentioning
confidence: 99%